ASSESSMENT OF RELIABILITY IN THE WATER BALANCE OF MILLS: CASE STUDY IN THE MINING SECTOR - Andrade Veloso Cruz, Irlana (Journal of Interdisciplinary Debates, 2024)
The thesis presented will talk about carrying out a reliability study applied to the water balance of Moinhos, where a proposal for intervention in a mining company will be shown. The importance of the reliability study will also be analyzed, since the loss of water through leaks resulting from excess pressure is a major obstacle in the management of water supply systems. Thus, this study revolves around responding to climatological aspects that affect water balance variables. This work is justified by the importance of carrying out a reliability study on the water balance of Moinhos, aiming to know the water availability in the region. The general objective of this dissertation is to present a proposal for a densimeter installation service to control the water balance of Moinhos in a mining company. In the specific objectives, concepts about the objects of study of the research will be presented, in addition to investigating the energy consumption by the studied company, describing the process of installing densimeters, until the evaluation of the expected results. The methodology used to carry out this study will be qualitative and bibliographic research.